Sosialisasi dan Tutorial Diversifikasi Produk Olahan Mangrove (Sirup Mangrove) di Desa Cibitung, Sukabumi - Alifah Fidela; Dewa Made Juli Santika; Jonson Lumban; Fis Purwangka (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The business of processing mangroves into food products does not seem to have been developed and attracted by coastal communities. Many people do not know that mangroves can be consumed and the bark can be used as fabric coloring. Knowledge about the potential and benefits of mangroves as a food source is still very little and not widely known. Pedada is one type of mangrove that grows abundantly throughout the coastal areas of Indonesia. Therefore, this program aims to process mangroves into processed food products. The method used in this program is a trial of making mangrove syrup, mangrove-related socialization, and mangrove fruit processing demo. The results show that one of them mangrove fruit can be processed into beverage products one of which is syrup. The resulting syrup has a sweet and sour taste that is fresh and so much liked. Also, Pedada syrup is believed to have many health benefits including being able to increase body stamina, stimulate libido and increase appetite. Keywords: product diversification, mangrove, syrup